Short hydrogen bonds in the catalytic mechanism of serine proteases - VLADIMIR LESKOVAC (Journal of the Serbian Chemical Society, 2008)
The survey of crystallographic data from the Protein Data Bank for 37 structures of trypsin and other serine proteases at a resolution of 0.78–1.28 Å revealed the presence of hydrogen bonds in the active site of the enzymes, which are formed between the catalytic histidine and aspartate residues and are on average 2.7 Å long. This is the typical bond length for normal hydrogen bonds. The geometric properties of the hydrogen bonds in the active site indicate that the H atom is not centered between the heteroatoms of the catalytic histidine and aspartate residues in the active site. Taken together, these findings exclude the possibility that short “low-barrier” hydrogen bonds are formed in the ground state structure of the active sites examined in this work. Some time ago, it was suggested by Cleland that the “low-barrier hydrogen bond” hypothesis is operative in the catalytic mechanism of serine proteases, and requires the presence of short hydrogen bonds around 2.4 Å long in the active site, with the H atom centered between the catalytic heteroatoms. The conclusions drawn from this work do not exclude the validity of the “low-barrier hydrogen bond” hypothesis at all, but they merely do not support it in this particular case, with this particular class of enzymes.